Pengembangan Kurikulum Bidang Studi Pendidikan Agama Islam Pada Program Akselerasi di SMAN 5 Surabaya - Ishmatun Nihayah (Nazhruna: Jurnal Pendidikan Islam, 2018)
In this study we focus on two things; the first is the implementation of acceleration program in SMAN 5 Surabaya, the second is the curriculum development in the field of study of Islamic Religion in the acceleration program in SMAN 5 Surabaya. To obtain answers from both research focuses, we use qualitative descriptive method. The data source applies triangulation, namely documentation, observation and interviews. Documentation techniques are used to obtain data about documents I and document II, then we use observation and interview techniques to find the data about the situation, conditions, and circumstances of the school (starting from the environment, student activities, student behavior, learning process, etc.).